Breast surgery for young women with early-stage breast cancer: Mastectomy or breast-conserving therapy?. Issue 18 (7th May 2021) - Sun, Zhi-Hong; Chen, Chuang; Kuang, Xin-Wen; Song, Jun-Long; Sun, Sheng-Rong; Wang, Wei-Xing
Abstract : Abstract: Whether breast-conserving therapy (BCT) should be chosen as a local treatment for young women with early-stage breast cancer is controversial. This study compared the survival benefits of BCT or mastectomy in young women under 40 with early-stage breast cancer and further explored age-stratified outcomes. This study investigated whether there is a survival benefit when young women undergo BCT compared with mastectomy. The characteristics and prognosis of white women under 40 with stage I–II breast cancer from 1988 to 2016 were analyzed using the Surveillance, Epidemiology, and End Results (SEER) database. These women were either treated with BCT or mastectomy. The log-rank test of the Kaplan–Meier survival curve and Cox proportional risk regression model were used to analyze the data and survival. The analysis was stratified by age (18–35 and 36–40 years). A total of 23, 810 breast cancer patients were included, of whom 44.9% received BCT and 55.1% underwent mastectomy, with a median follow-up of 116 months. Patients undergoing mastectomy had a higher tumor burden and younger age. By the end of the 20th century, the proportion of BCT had grown from nearly 35% to approximately 60%, and then gradually fell to 35% into the 21st century. Compared with the mastectomy group, the BCT group had improved breast cancer-specific survival (BCSS) (hazard ratio [HR] 0.917; 95% CI, 0.846–0.995, P  = .037) and overall survival (OS) (HR 0.925; 95% CI, 0.859–0.997, P  = .041). In stratified analysis according to the different ages, the survival benefit of BCT was more pronounced in the slightly older (36–40 years) group while there was no significant survival difference in the younger group (18–35 years). In young women with early-stage breast cancer, BCT showed survival benefits that were at least no worse than mastectomy, and these benefits were even better in the 36 to 40 years age group. Young age may not be a contraindication for BCT.